Experimental investigation of dodecylbenzene sulfonic acid and toluene dispersants on asphaltene precipitation of dead and live oil. (3rd April 2017) - Zahedi, E.; Vafaie-Sefti, M.; Shadman, M. M.; Naderi, H.; Amiri, M.; Noorbakhsh, A.
ABSTRACT: Asphaltene is the heaviest fraction of oil, and if the thermodynamic conditions of oil change, it can be separated from oil precipitate. Of common methods for preventing asphaltene precipitation, using predictive methods, biological methods and injection of dispersants can be mentioned. In this study, the effect of two dispersants of toluene and dodecylbenzene sulfonic acid on asphaltene precipitation of a dead and a live oil sample has been investigated. According to the results, these dispersants in dead oil create an optimum point for asphaltene precipitation. In live oil, these dispersants reduce asphaltene precipitation down to 70%. In addition, it was observed that as an effect of injecting these dispersants, the average sizes of asphaltene flocculation have reduced.